Net Capital Flows and Portfolio Diversification - Constantin Bürgi; Vida Bobic; Min Wu (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper presents a new explanation for the sustained pattern of international net capital flows by modifying the standard consumption capital asset pricing model (CCAPM) to create net capital flows beyond the initial period. In addition to the well established link between asset returns and the cyclical correlation between countries in standard CCAPM models, our model links asset flows to the cyclical correlation. In particular, the model predicts that a country that has a low correlation with the global cycle should see net capital inflows. We provide strong empirical evidence in support of this link and a 0.1 increase in the correlation leads to a 0.5-0.7 percentage point decrease in the net capital inflows as a % of GDP.
Keywords: F36; F43; 330; net capital flows; productivity; growth; portfolio diversification